Ischemic stroke following Dengue fever: A case report - Manappallil, Robin George (Asian Journal of Medical Sciences, 2015)
Dengue fever is an acute febrile illness associated with severe headache, myalgias, arthralgias, rashes, leucopenia and thrombocytopenia. Occasionally unusual haemorrhage such as gastrointestinal bleeding, intracranial haemorrhage, hypermenorrhoea, hematuria and massive epistaxis occur. This is a case of an elderly male with dengue fever who presented with ischemic stroke. Asian Journal of Medical Sciences Vol.7(2) 2015 107-108